Synthesis and characterization of Fulvestrant and Paclitaxel conjugates with polyamidoamine dendrimer fourth generation - Wróbel, Konrad; Wołowiec, Stanisław (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Poorly soluble anticancer drugs can be attached covalently into biologically inert macromolecule in order to administrate a drug as water soluble form. It was proven that covalent linkers, for instance amide or carbamate bonds are susceptible to hydrolysis. Thus the attached drug can be released from the conjugates in tissue, specifically within the targeted cell. We aimed at construction of water soluble conjugates of Fulvestrant and Paclitaxel with PAMAM G4 dendrimer. In order to obtain water soluble conjugates the amine groups were substituted with R-glycidol. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Polyamidoamine dendrimer of fourth generation was synthesized and examined by detailed NMR analysis in water and in DMSO. The conjugates were covalently linked to amine groups of PAMAM after activation of Fulvestrant 17-OH group with 4-nitrophenylchloroformate and activation of end-carboxyl group of Paclitaxel succinate. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The method of binary conjugate PAMAMG4-Fulvestrant-Paclitaxel synthesis was elaborated and the product was characterized by physicochemical methods. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The glycidylated PAMAMG4-Fulvestrant-Paclitaxel conjugate is better soluble in water than unconverted drugs.